Distal Consequences of Oral Inflammation - Konkel, Joanne E.; O'Boyle, Conor; Krishnan, Siddharth (Frontiers in Immunology, 2019)
Periodontitis is an incredibly prevalent chronic inflammatory disease, which results in the destruction of tooth supporting structures. However, in addition to causing tooth and alveolar bone loss, this oral inflammatory disease has been shown to contribute to disease states and inflammatory pathology at sites distant from the oral cavity. Epidemiological and experimental studies have linked periodontitis to the development and/or exacerbation of a plethora of other chronic diseases ranging from rheumatoid arthritis to Alzheimer’s disease. Such studies highlight how the inflammatory status of the oral cavity can have a profound impact on systemic health. In this review we discuss the disease states impacted by periodontitis and explore potential mechanisms whereby oral inflammation could promote loss of homeostasis at distant sites.